CHARACTERISTICS OF FRACTURES OF THE UPPER JAW (World Bulletin of Public Health, 2024)
The article analyzes the conclusions of forensic medical examinations prescribed for fractures of the upper jaw. In all cases, fractures of the upper jaw were open, as well as single and bilateral. In unilateral fractures of the upper jaw, the fracture line passed sagittal along the palatine suture. The displacement of bone fragments in fractures of the upper jaw depends on the force and direction of impact; on the mass of the fragments themselves; on the traction force of the chewing (pterygoid) muscles. The high informativeness of both radiography and computed tomography in the examination of persons with jaw fractures was noted.